La educación musical en el nivel primario, y su incidencia en la práctica coral infantil en los estudiantes de tercero, cuarto y quinto año de educación básica de la escuela fiscal mixta “Manuel Benjamín Carrión” de la ciudad de Loja, periodo abril-noviembre 2011 - Luna Viñamao, Norman Orlando (2015)
By developing this investigation began with a general objective that leads us to analyze the impact of music education in the development of children's choral skills in students in third, fourth and fifth year of basic education of the Joint Public School ¨ Manuel Benjamín Carrión de Loja. In fulfilling mentioned objective technical survey and interviews were used to obtain necessary data from the population investigated. Continuing the research process methods that helped us discover was used, the problem, presenting hypotheses and providing solutions among the main methods are: the scientific method, descriptive method, deductive and inductive method. Joint Fiscal school Manuel Benjamín Carrión de Loja was open to work hard against his problem, poor children's choir practice scenario. Visit students in third, fourth and fifth years of basic education, in order to select voices to prepare by classes after hours and they create a children's choir choral giving opening practice: actions as developed. The results we expected to obtain, were exactly as anticipated by the hypothesis. A mixed children's choir was established, with the participation of students selected third, fourth and fifth years of the Joint Fiscal school "Manuel Benjamín Carrión" of the city of Loja, where the children's choir practice applies. In conclusion the awakened interest in children is reflected by knowing and exercising the children's choir practice and recommended for inclusion in music lessons, exercises that promote choral practice.